Caregiver Coping Mechanisms on the Ability to Care for Individual with Schizophrenia (IWS) - Dwi Heppy Rochmawati; Betie Febriana; Hetty Catur Ellyawati (Indonesian Journal of Global Health Research, 2022)
The health condition of individual with schizophrenia (IWS) needs special attention because it shows a high number and has a bad impact on IWS and caregivers and families. Meanwhile, the handling of IWS takes a long time and causes the caregiver's self-defense to weaken and decrease. Purpose to determine the relationship between coping mechanisms and the caregiver's ability to treat IWS. Method using a non-experimental quantitative research design with a cross sectional method. Sampling was done by total sampling with a total sample of 53 caregivers. Data was collected using a questionnaire on coping mechanisms and cognitive and psychomotor abilities and then analyzed by univariate and bivariate. Univariate analysis using frequency distribution, bivariate analysis using chi-square test. Mean age 41-60 years 69.8%; female 94.3%; high school education below 92.4%; caregiver working as a laborer 66%, relationship with IWS as a parent 66% and length of care >10 years 41.5%. As many as 64.2% of caregivers have adaptive coping mechanisms, caregivers know how to treat IWS 75.5% and are able to care for 54.5% quite well. Data analysis using chi-square test showed that there was a relationship between coping mechanisms and cognitive abilities (p-value 0.019), there was a relationship between coping mechanisms and psychomotor abilities (p-value 0.001). There is a relationship between caregiver coping mechanisms and the ability to care for IWS, caregivers need to get help to improve psychomotor abilities in providing care for IWS